Implementasi ORESTE dengan Basson Rank untuk pemilihan tempat kursus TOEFL di Yogyakarta - Femi Dwi Astuti; Siska Lidya Revianti (bit-Tech, 2023)
TOEFL is one of the most frequently used international standardized tests for registering for masters and doctoral degrees, seeking study scholarships or for promotions. Unfortunately, there are still many students and employees who still experience difficulties in taking the TOEFL test. This is what then becomes the reason for them to take English courses, especially to prepare themselves for preparing the TOEFL test. Yogyakarta, which has the title of "Student City", has many campuses and many English courses that offer the TOEFL Preparation Course. There are many types of TOEFL formats and many TOEFL Preparation Programs are offered by English courses in Yoggyakarta. The TOEFL Preparation courses has various programs including different price, teacher competencies, and facilities. In this study, the ORESTE method was used to help the people determining the best course according to its ranking. This method is one of the Multiple Attribute Decision Making (MADM) methods used to find alternatives using predetermined criteria and preference weights. The criteria used are price, instructor, materials, facilities and location. The results showed that the best TOEFL course ranking/order alternative was A16 with a preference score of 3.9425 and the course with the lowest score was A4 with a score of 9.878177.